Pengaruh Literasi Keuangan dan Penggunaan Financial Technology terhadap Keputusan Investasi pada Masyarakat Usia Produktif di Kecamatan Mande, Kabupaten Cianjur - Nofia Lailatul Q.; Dadang Agus Suryanto (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
Investment decisions are one of the important aspects of financial management among the productive-age population, as they are closely related to achieving future financial well-being. However, individuals' ability to make investment decisions is influenced by various factors, including financial literacy and the use of financial technology. This study aims to analyze the effect of financial literacy and the use of financial technology on investment decisions among the productive-age population in Mande District, Cianjur Regency. This study employed a quantitative approach using a causal-associative research method. The sample consisted of 100 respondents selected through purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that financial literacy and the use of financial technology partially have a positive and significant effect on investment decisions. Meanwhile, simultaneously, financial literacy and the use of financial technology have a significant effect on investment decisions. The findings of this study are expected to serve as a reference for the community to improve financial literacy and optimize the use of financial technology in making investment decisions.